The Role of Leadership in the Management of Regional Government Organizations (Study: Organizational Bureau of the Regional Secretary of Southwest Papua Province) - Foni Flora Way; Susetyowati Sofia; Akmal Ridwan (www.amertainstitute.com, 2025)
This qualitative study investigates the role of leadership in managing regional government organizations, focusing on the Organization Bureau of the Regional Secretariat (SETDA) of Southwest Papua Province—Indonesia's 38th and newest province. This research aims to: (1) explore the role of the Bureau Head in overseeing organizational management; (2) identify factors that contribute to leadership transformation; and (3) examine the strategies and steps adopted by the Bureau Head in responding to internal and external organizational changes. Data were collected through semi-structured interviews with six key informants, including the Bureau Head, structural and functional subordinates, and executive staff. The findings show that the Bureau Head exercises a delegative-democratic leadership style, which encourages participation, empowers subordinates, and aligns responsibilities with defined roles (tupoksi). This leadership model fosters adaptability, enhances decision-making quality, and drives organizational innovation. As a newly formed region, Southwest Papua faces unique bureaucratic challenges, including resource limitations, legal restructuring, and human capital development. The role of leadership in this transitional context becomes crucial not only in managing resources but also in cultivating an institutional culture that supports reform, accountability, and sustainable public service delivery. The study highlights the transformative impact of responsive and situational leadership in building administrative capacity and facilitating regional autonomy.